Determinants of and Willingness to Use and Pay for Digital Health Technologies Among the Urban Elderly in Hangzhou, China - Yang K; Li Y; Qi H (Dove Medical Press, 2023)
Keng Yang,1,2 Yang Li,3 Hanying Qi4,5 1Institute of Economics, Tsinghua University, Beijing, People's Republic of China; 2One Belt-One Road Strategy Institute, Tsinghua University, Beijing, People's Republic of China; 3Wuyi University, Jiangmen, People's Republic of China; 4The New Type Key Think Tank of Zhejiang Province "China Research Institute of Regulation and Public Policy", Zhejiang University of Finance and Economics, Hangzhou, People's Republic of China; 5China Institute of Regulation Research, Zhejiang University of Finance and Economics, Hangzhou, People's Republic of ChinaCorrespondence: Hanying Qi, Zhejiang University of Finance and Economics, Hangzhou, 310018, People's Republic of China, Tel +86 151 5802 5275, Email qihanying90@zufe.edu.cnPurpose: In recent years, little research has been conducted on the willingness to use and pay for digital health technologies for elderly people. Thus, this study investigates the willingness to use and pay for digital health technologies and their influential factors among urban elderly in Hangzhou, China.Methods: A structured questionnaire was completed by 639 older adults from 12 communities in Hangzhou. This paper presents a descriptive statistics analysis and performs a multivariate regression to identify the determinants of willingness to use and pay for digital health technologies among the elderly.Results: The result shows the percentage of participants who chose very willing (3.6%) and partly willing (10%) to use was lower than those who were less unwilling (26.4%) and not willing (27.1%) to use. The percentage of participants who are unwilling (less unwilling,30.5%; not willing, 39.7%) to pay for digital health technology is even higher. The regression results show that age, working status, exercise and physical activity, medical insurance, income, life satisfaction and history of illness were significantly associated with willingness to use digital health technology among urban elderly. On the other hand, age, exercise status, income and history of illness were significantly associated with willingness to pay for digital health technologies among older adults.Conclusion: The overall willingness to use and pay for digital health technologies are low among urban older people living in Hangzhou. Our results have important implications for digital health policy making. Practitioner and regulator should develop strategies to improve the supply of digital health technology services to meet different demands of the elderly with different age, working status, exercise and physical activity, medical insurance, income, life satisfaction and history of illness. And medical insurance would be an important instrument to facilitate digital health development.Keywords: digital health, elderly healthcare, willingness to use, willingness to pay